The Lived Experience of Inequalities in the Provision of Treatment for Hepatitis C - Skyrme, Sarah Louise (Frontiers in Sociology, 2021)
The issues of health, illness, stigma and inequalities in healthcare provision, areas that in my role as a social researcher were already of interest and concern, shifted to a different perspective when I was diagnosed with hepatitis C. From this altered position, my body and lifeworld were a nexus point for a range of ongoing challenges around staying as well as possible, and the struggle to get my healthcare needs met. There is a gap between the support provided for some ill and disabled people, and the help that they actually require. This is particularly so for conditions that are not well understood, that have a low public profile, limited funding, and/or are in some way stigmatised due to perceived differences to social norms. Hepatitis C is one such condition, it is a viral disease that is transmitted through blood-to-blood contact and it causes ongoing damage to the liver. Because of the systemic nature of the disease, individuals may struggle to cope with the demands of work and daily living, and their lifeworld and opportunities are frequently limited. It can be challenging for the patient to advocate for themselves due to low energy levels, self-blame for getting ill, and the stigma associated with the condition. The first generation of effective anti-viral drugs emerged from clinical trials in 2013, but in the United Kingdom context, access was only possible for those with advanced liver disease. Therefore, many patients felt compelled to purchase the anti-virals through Buyers Clubs, whereby generic versions of the drugs are imported for personal use at a fraction of the market cost. In this article I draw on my own lived experience of joining a Buyers Club as an example of how risks and benefits are weighed, and to explain the contexts in which decisions are shaped and made.